Changes in gastrointestinal lymph and blood vessels in patients with cirrhotic portal hypertension - Ikeda, Rie; Michitaka, Kojiro; Yamauchi, Yuusuke; Matsui, Hidetaka; Onji, Morikazu (Journal of gastroenterology, 2001)
The aim of this study was to characterize the lymph vessels in different parts of the gastrointestinal tract and also to evaluate morphometric changes in these vessels during cirrhotic portal hypertension. Sixteen patients with cirrhotic portal hypertension and 18 control subjects without portal hypertension were enrolled in the study. Tissue specimens were collected at autopsy or surgery, and were stained enzyme histochemically, using 5'-nucleotidase and alkaline phosphatase to distinguish lymph vessels and blood vessels, respectively. The numbers of vessels and their luminal areas were estimated using computer graphics software (National Institutes of Health [NIH] image program). The numbers and luminal areas of the lymph vessels varied considerably among the different organs of the gastrointestinal tract, both in controls and in the patients with cirrhotic portal hypertension. There was no significant difference in the numbers of lymph vessels between controls and patients with cirrhotic portal hypertension. However, the luminal area of the lymph vessels in the esophagus and stomach was significantly greater in the patients with cirrhotic portal hypertension than in the controls. These differences in lymph vessels were not seen in the small intestine and colon. These data indicate that dilatation of lymph vessels may be related to the absorption of excess interstitial fluid, resulting from congestion, in cirrhotic portal hypertension.